Properties of Street Food Rolled Eggs in Padang City - Muhaimin Simatupang; Afriani Sandra; Intan Dwi Anggraini; Aronal Arief Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Rolled eggs are a popular type of street food among schoolchildren. Consumption of this product has become controversial regarding nutrition and health, particularly its high-fat content (oily), the potential for oxidation from the use of bulk oil and reused oil, and the potential for contamination due to its production location on the side of the road. This study aims to determine the physicochemical and microbiological quality of rolled eggs sold in Gunung Pangilun Village, North Padang District, Padang City. Fat content, free fatty acids, peroxide value, pH, color (L*, a* b*), total bacterial colonies, and total Escherichia coli colonies were the parameters measured. The study used a Randomised Block Design (RBD) with four egg roll vendors as treatments and five repetitions of sample collection. The results showed that the range of fat content, free fatty acids, and peroxide values was 22.10–36.48%, 0.56–0.61%, and 27.26–33.05 meq/kg, respectively. Meanwhile, the total plate count ranged from 5.08 to 24.76 x10⁷ repercussion CFU/g, and the total E. coli count ranged from 3.32 to 29.24 x10⁵ repercussion CFU/g. Physically, the color of the rolled eggs showed ranges of lightness, redness, and yellowness of 53.81–57.23, 1.83–3.25, and 16.09–19.86, respectively, and a pH range of 8.45–8.51. Based on the chemical and microbiological analysis results of the rolled egg samples, there is a relatively high level of contamination and chemical damage. It indicates caution when consuming rolled eggs, as excessive consumption may lead to health issues.